Framework for assessing the climate vulnerability of unpaved roads in Sierra Leone - Kamara, Phodie Musa; Tuffour, Yaw Adubofour; Baffour-Ata, Frank; Obeng, Daniel Atuah (Frontiers in Climate, 2025)
IntroductionUnpaved roads make up 80% of the global road network and 90% in developing countries. In Sierra Leone—one of the world’s most climate-vulnerable nations—secondary unpaved roads account for 96% of the core network, serving as vital links for rural access, markets, and social inclusion. Yet, no structured framework currently guides the management of climate risks to these roads.MethodsThis study reviewed international climate risk and vulnerability assessment frameworks and identified their limited applicability in resource-constrained contexts due to heavy data demands, proprietary software, and high computing requirements. To address this gap, a five-phase, context-specific framework was developed, adapted from the IPCC vulnerability model. The framework employs cost-effective, open-source tech tools (QGIS, QField, PostGIS, cloud storage, and Microsoft Power BI) and integrates index-based, spatial, and stakeholder-driven approaches to generate composite indicators of road condition deficiency, maintenance efficacy, and roads’ criticality.ResultsApplication of the framework in Sierra Leone demonstrated its ability to identify climate-vulnerable unpaved road segments and highlight priority areas for adaptation. The framework proved practical under local data and institutional constraints, avoiding reliance on costly proprietary tools or high-end computing infrastructure.DiscussionNationally, the framework offers the first structured approach for integrating climate resilience into road management in Sierra Leone, supporting the National Roads Agency. Globally, it contributes a transferable, resource-efficient, and community-driven methodology for embedding climate adaptation into transport planning across the Global South. It aligned with national and international policies (Sierra Leone National Adaptation Plan (NAP), Sierra Leone Nationally Determined Contributions (NDC), UN Sustainable Development Goas (SDGs 9, 11 and 13).